Correlation of the Myocardial Viability Score with Left Ventricular Ejection Fraction in Patients after Revascularization - Viktoriia V. Kundina; Tetiana M. Babkina (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. Coronary artery disease (CAD) is one of the main causes of cardiovascular death. The severity of CAD is determined by the left ventricular (LV) dysfunction which is caused by coronary atherosclerosis. The possibility of restoring functional capacity of the heart (ejection fraction (EF)) depends on hibernating volume of the myocardium which is a pitfall in revascularization.The aim. To assess the correlation between the score of the viable myocardium (VM) and EF with systolic dysfunction and preserved LVEF in patients after coronary artery bypass grafting (CABG).Material and methods. To implement the set clinical tasks, 62 patients with CAD with preserved systolic function and systolic dysfunction were examined, 35 (56%) patients had heart failure with an EF of 49% (group 2) and less. Twenty-seven (44%) patients had preserved ventricular function of 50% or more (group 1). The mean age of the subjects was 59.6 ± 8.2 years. Five (8.0%) patients denied myocardial infarction. Myocardial scintigraphy was performed on Infinia Hawkeye all purpose imaging system (GE, USA) with integrated CT. The studies were performed in SPECT and SPECT/CT with ECG synchronization (gated SPECT) modes. 99mTc-MIBI with an activity of 555–740 MBq was used. Myocardial scintigraphy was performed in the course of treatment (before CABG and after CABG) according to the One Day Rest protocol. A total of 124 scintigraphic studies were performed.Results and discussion. Samples of the studied patients “before” and “after” treatment were compared using Wilcoxon matched-pairs test. In group 1 in patients with EF ≥ 50% the score of VM increased after CABG with values from 81.7 CI 95% [78.5; 84.9] to 86.9 CI 95% [84.4; 89.3]. However, the EF itself before and after treatment remained the same or slightly decreased amounting to 54.9 CI 95% [50.8; 59.1] and 52.5 CI 95% [48.6; 56.3]. In group 2 in patients with EF ≤ 49% the amount of VM increased after CABG with values from 59.9 CI 95% [54.9; 64.8] to 65.9 CI 95% [60.2; 71.6] (p = 0.00005). However, the EF itself before and after treatment remained the same, amounting to 28.9 CI 95% [24.8; 32.9] and 31.1 CI 95% [26.8; 35.5] (p = 0.19).Conclusions. Myocardial viability in both study groups significantly improved, given the high statistical reliability of the results, although LVEF either remained unchanged or changed slightly. Improvement of static parameters (wall perfusion) also confirms positive effect of revascularization with constant dynamic parameters (EF, end-diastolic volume) or statistically insignificant changes thereof. There is no direct correlation between VM and EF.